Broad Adaptability of Coronavirus Adhesion Revealed from the Complementary Surface Affinity of Membrane and Spikes - Aritz B. García‐Arribas; Pablo Ibáñez‐Freire; Diego Carlero; Pablo Palacios‐Alonso; Miguel Cantero‐Reviejo; Pablo Ares; Guillermo López‐Polín; Han Yan; Yan Wang; Soumya Sarkar; Manish Chhowalla; Hanna M. Oksanen; et al. (Advanced Science)
Abstract Coronavirus stands for a large family of viruses characterized by protruding spikes surrounding a lipidic membrane adorned with proteins. The present study explores the adhesion of transmissible gastroenteritis coronavirus (TGEV) particles on a variety of reference solid surfaces that emulate typical virus‐surface interactions. Atomic force microscopy informs about trapping effectivity and the shape of the virus envelope on each surface, revealing that the deformation of TGEV particles spans from 20% to 50% in diameter. Given this large deformation range, experimental Langmuir isotherms convey an unexpectedly moderate variation in the adsorption‐free energy, indicating a viral adhesion adaptability which goes beyond the membrane. The combination of an extended Helfrich theory and coarse‐grained simulations reveals that, in fact, the envelope and the spikes present complementary adsorption affinities. While strong membrane‐surface interaction lead to highly deformed TGEV particles, surfaces with strong spike attraction yield smaller deformations with similar or even larger adsorption‐free energies.